A Simplified Representation of Pressure Flow from Surface Slopes in Urban Sewer Systems - Huabing Huang (Water, 2020)
A Constant Pipe Drainage (CPD) capacity for sewer systems is commonly applied when undertaking flood risk assessment, however data that are needed for calibration and validation of numerical models are scarce or unavailable. The CPD model neglects the effect of pressure flow and leads to significant deviation in flood volume estimate. This study proposes a new index Velocity Ratio (VR) to approximate pressure flow. A case study in Guangzhou, China is used to investigate the capability of reproducing a reasonable flood volume for two models, the CPD and the VR-based. Compared to the flood volume simulated by the Storm Water Management Model (SWMM), the CPD model shows a significant overestimation, Mean Relative Deviation (MRD) 192%. The VR-based model has a much better performance, MRD 18%. Therefore, the VR-based model is a simple and effective representation of pressure flow in urban sewer systems and can be easily applied in areas lacking detailed pipe data, especially for planning new pipe networks or updating the old pipes.